Ground Heat Exchangers-A Review - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2004)
The temperature distribution in the ground is distinguished in three zones. The Surface zone, which reaches a depth of about 1m, the Shallow zone extending at a maximum depth of 20 m, and the Deep zone, where the ground temperature remains nearly constant throughout the year. To effectively exploit the heat capacity of the soil a heat-exchanger system has to be constructed. Usually an array of buried pipes running along the length of the building, a nearby field or buried vertically into the ground is utilised. A circulating fluid (water or air) is used in summer to extract heat from the hot environment of the building and dump it into the ground and vice versa in winter. A heat pump may also be coupled to the ground heat exchanger to increase its efficiency. In the literature several calculation models are found for ground heat exchangers. One-dimensional models were devised in the first stages of the system study which were replaced by two-dimensional models during the nineties and three-dimensional systems during the recent years. The present models are further refined and can accept any type of grid geometry that may give greater detail of the temperature variation around the pipes and in the ground. Monitoring programs have been set-up to test various prototype constructions with satisfactory results.
Keywords: Temperature distribution; Ground; Grid geometry